Non-traditional exports and their relationship with Peru's trade balance - Cruz Hidalgo, Lady Stefania; Rodríguez Abraham, Antonio Rafael (LACCEI, 2025)
This research evaluated the relationship of non-traditional exports on the Peruvian trade balance (2018-2023) using a quantitative, applied and descriptive approach, with a longitudinal non-experimental design. A significant moderate-to-high positive correlation (Spearman's Rho = 0.677, p-value < 0.01) was found between the two variables, based on 72 monthly data. The results showed that non-traditional exports contribute significantly to the trade surplus, generating stable income and reducing dependence on traditional products. Despite logistical challenges and limited government support during COVID-19, key sectors such as agribusiness showed sustainable growth, strengthening Peru's trade balance.